Estimation of Cholesterol and Bile Acid Turnover in Man by Kinetic Analysis - Quarfordt, Steven H. (1973)
The kinetics of cholesterol and bile acid turnover were determined from an analysis of the biliary lipids after a single intravenous injection of labeled cholesterol. A compartmental model was designed for the system, and the fractional metabolic rates and fluxes were determined in one lean and two obese normal humans. Each of the normals converted about 3% per day of their rapidly miscible cholesterol pool to cholic acid and 1% per day or less to chenodeoxycholate. Cholate was catabolized at about twice the rate of the dihydroxy bile acids in these normals. Two of the normals were fed corn oil with little change in their kinetic parameters from the control state. The other normal received cholestyramine and dramatically increased the bile acid flux with little change in neutral sterol catabolism. A cirrhotic patient was also studied by this technique and noted to have kinetic parameters quite different from the normals.